Early-Stage Glottic Squamous Cell Carcinoma in the Era of Image-Guided Radiotherapy - Gupta, Amit; Wong, Kee Howe; Newbold, Kate; Bhide, Shreerang; Nutting, Chris; Harrington, Kevin Joseph (Frontiers in Oncology, 2021)
Early-stage squamous cell cancer (SCC) of the glottis has a good prognosis. Therefore, patients have long survival outcomes and may potentially suffer from late toxicities of radiotherapy. Radiotherapy with a conventional parallel-opposed-pair or anterior-oblique beam arrangements for stage 1 and 2 glottic SCC have field borders that traditionally cover the entire larynx, exposing organs-at-risk (e.g. carotid arteries, contralateral vocal cord, contralateral arytenoid and inferior pharyngeal constrictor muscles) to high radiation doses. The potential long-term risk of cerebrovascular events has attracted much attention to the dose that carotid arteries receive. Swallow and respiratory motion of laryngeal structures has been an important factor that previously limited reduction of the radiation treatment volume. Motion has been evaluated using multiple imaging modalities and this information has been used to calculate PTV margins for generation of more limited target volumes. This review discusses the current literature surrounding dose-effect relationships for various organs-at-risk and the late toxicities that are associated with them. This article also reviews the currently available data and effects of laryngeal motions on dosimetry to the primary target. We also review the current limitations and benefits of a more targeted approach of radiotherapy for early-stage glottic SCCs and the evolution of CT-based IGRT and MR-guided radiotherapy techniques that may facilitate a shift away from a conventional 3D-conformal radiotherapy approach.